2019
DOI: 10.17060/ijodaep.2019.n1.v4.1607
|View full text |Cite
|
Sign up to set email alerts
|

La salud mental en los portugueses de enseñanza superior frente a la transición al mercado de trabajo

Abstract: En el actual entorno de crisis económica y del agravamiento del desempleo, la preocupación es, sobre todo, con el deterioro de la salud mental de los estudiantes universitarios que saldrán al mercado laboral, ya que esta transición plantea problemas a nivel de la salud mental de los estudiantes universitarios, contribuyendo al desarrollo de niveles más elevados de ansiedad y de estrés.Este artículo es una síntesis de un estudio de investigación que trata de determinar la existencia de una relación entre la sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(2 reference statements)
0
1
1
Order By: Relevance
“…Moreover, the gender variable predicts the risk of suffering emotional disorders among university students, as the fact of being a woman significantly increased the risk of suffering emotional disorders by 63.7%. This result differs from other similar studies in which no significant differences were found with regard to gender [11,27]. Therefore, being a woman and having high levels of negative affect predict the risk of suffering emotional disorders, while greater happiness and a better perception of health decrease this risk.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Moreover, the gender variable predicts the risk of suffering emotional disorders among university students, as the fact of being a woman significantly increased the risk of suffering emotional disorders by 63.7%. This result differs from other similar studies in which no significant differences were found with regard to gender [11,27]. Therefore, being a woman and having high levels of negative affect predict the risk of suffering emotional disorders, while greater happiness and a better perception of health decrease this risk.…”
Section: Discussioncontrasting
confidence: 98%
“…However, the changes and transformations that have occurred in the university system over the last few years have transformed the university activities, for both lecturers and students, making the work outlook more stressful [9,10]. In the studies carried out with universities, some indicate that the average age for the start of mental health problems is between 18 and 24 years of age [11,12]. One of the possible explanations [13] not only refers to the changes that occur during adolescence, but also the challenges they face upon entering university.…”
Section: Introductionmentioning
confidence: 99%